Penggunaan Media Short Movie dalam Pembelajaran Kata Baku Bahasa Indonesia Siswa Kelas IV Sekolah Dasar Tri Guna Bhakti Surabaya - Ramadhan, Ilyas Dwi; Pance Mariati; Rudi Umar Susanto; Syamsul Ghufron (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The factor that causes students' low understanding of standard words is the lack of application of media carried out in learning about standard words. Teachers usually only use LKS or thematic books in delivering learning materials, especially standard word materials. At this time Indonesian is sometimes pronounced well and correctly. Caused by the surrounding environment that is difficult to apply in everyday life. Indonesian is very important in everyday life for pronunciation and writing. The purpose of this study is todescribe the use of Short Movie media in learning standard words grade IV SD Tri Guna Bhakti and describestudents' mastery of standard words after learning using Short Movie learning media. The object of this study was grade IV students at SD Tri Guna Bhakti Surabaya totaling 28 students. This research method uses qualitative descriptive research methods. Research with this approach aims to provide a detailed, thorough, and contextual picture of the phenomenon under study. The data collection method used by the author is observation and interview. Based on the results of the research conducted, it was concluded that by using Short Movie media in learning standard words Indonesian, grade 4 students at SD Tri Guna Bhakti Surabaya can be actively involved, visualize the use of standard words in relevant contexts, and develop understanding and application of standard words in everyday life.